Hypothalamic Crh/Avp, Plasmatic Glucose and Lactate Remain Unchanged During Habituation to Forced Exercise - Toval, Angel; Vicente-Conesa, Francisco; Martínez-Ortega, Paloma; Kutsenko, Yevheniy; Morales-Delgado, Nicanor; Garrigos, Daniel; Alonso, Antonia; Ribeiro Do Couto, Bruno; Popović, Miroljub; Ferran, José Luis (Frontiers in Physiology, 2020)
It has been demonstrated that physical activity contributes to a healthier life. However, there is a knowledge gap regarding the neural mechanisms producing these effects. One of the keystones to deal with this problem is to use training programs with equal loads of physical activity. However, irregular motor and stress responses have been found in murine exercise models. Habituation to forced exercise facilitates a complete response to a training program in all rodents, reaching the same load of physical activity among animals. Here, it was evaluated if glucose and lactate -which are stress biomarkers- are increased during the habituation to exercise. Sprague Dawley rats received an 8-days habituation protocol with progressive increments of time and speed of running. Then, experimental and control (non-habituated) rats were subjected to an incremental test. Blood samples were obtained to determine plasmatic glucose and lactate levels before, immediately after and 30 minutes after each session of training. Crh and Avp mRNA expression was determined by two-step qPCR. Our results revealed that glucose and lactate levels are not increased during the habituation period and tend to decrease towards the end of the protocol. Also, Crh and Avp were not chronically activated by the habituation program. Lactate and glucose, determined after the incremental test, were higher in control rats without previous contact with the wheel, compared with habituated and wheel control rats. These results suggest that the implementation of an adaptive phase prior to forced exercise programs might avoid non-specific stress responses.